Intertextual dialogues in Andrei Bitov's novel Pushkin house (Slavic Studies, 2024)
Starting from the theoretical and typological models of intertextuality, elaborated by Renate Lachmann, Gerard Genette, Dubravka Oraic-Tolic, Mark Currie, this study aims to interpret the intertextual layers in Andrei Bitov's novel Pushkin House. The interpretive focus is placed on three levels: on the intertextual object in the novel (the specific prototexts and the literary tradition as a global prototext); on the intertextual relations and procedures in the novel; as well as on the mnemonic functions and implications of the intertextual dialogues in the novel.
Keywords: intertextuality; postmodern novel; Andrei Bitov